Susceptibility of the mammary gland to carcinogenesis. II. Pregnancy interruption as a risk factor in tumor incidence. - Russo, J. (1980)
In the rat, pregnancy and lactation prior to carcinogen administration protect the mammary gland from developing carcinomas and benign lesions. In this study, the influence of pregnancy interruption versus full pregnancy and pregnancy plus lactation on the incidence of carcinomas and benign lesions was studied in the mammary glands of rats treated with 7,12-dimethylbenz(a)anthracene (DMBA). Fifty-nine Sprague-Dawley rats were separated into 5 groups: I) rats that had had one pregnancy and one lactation; II) rats that had had one pregnancy without lactation; III) rats that had had pregnancy interrupted at the 12th day of gestation; IV) age-matched virgin rats as a control Group I; and V) age-matched virgin rats as a control for groups II and III. The 5 groups received a single intragastric dose of DMBA (10 mg/100 g body weight), with the exception of 2 animals per group, which were killed 1 hour after an intraperitoneal injection of 2.5 mu Ci 3H-thymidine/g body weight. The number of labeled nuclei per 100 cells (DNA labeling index, LI) was counted in terminal end buds (TEBs), terminal ducts (TDs), and alveolar buds (ABs) of the glands. The number of structures and the DNA-LI were correlated with the incidence of tumors at 22 weeks after DMBA. Pregnancy, with or without lactation, resulted in elimination of TEBs and reduction in the DNA-LI of TDs and ABs. These groups did not develop carcinomas. After the interruption of pregnancy the mammary gland contained numerous TEBs, with a high DNA-LI; 77% of these animals developed carcinomas, and all of them developed benign lesions. Therefore, while pregnancy and lactation protected the mammary gland from developing carcinomas and benign lesions by induction of full differentiation, pregnancy interruption did not elicit sufficient differentiation in the gland to be protective, and these animals were at the same risk as virgin animals treated with the carcinogen.